2017
DOI: 10.1016/j.tate.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between entrepreneurial behavior and teachers' job satisfaction

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Chaudhary and Chaudhary (2017) added that entrepreneurship has been associated with traits like high risk-taking abilities and achievement orientation, and it appears that women cannot see their perceived characteristics in alignment with the traits required for starting an entrepreneurial venture successfully. The same pattern of gender differences, with females reporting lower levels of entrepreneurial behavior, was also found in a recent study with Brazilian teachers (Amorim Neto, Rodrigues, & Panzer, 2017).…”
Section: Introductionsupporting
confidence: 81%
“…Chaudhary and Chaudhary (2017) added that entrepreneurship has been associated with traits like high risk-taking abilities and achievement orientation, and it appears that women cannot see their perceived characteristics in alignment with the traits required for starting an entrepreneurial venture successfully. The same pattern of gender differences, with females reporting lower levels of entrepreneurial behavior, was also found in a recent study with Brazilian teachers (Amorim Neto, Rodrigues, & Panzer, 2017).…”
Section: Introductionsupporting
confidence: 81%
“…social needs" (Mair & Martı , 2005, p. 3). Teacher entrepreneurs are individuals who are less concerned about material gains (Amorim Neto et al, 2017) and more concerned about achieving positive social change (Sanchez, 2014).…”
Section: Social Value-oriented Teacher Entrepreneursmentioning
confidence: 99%
“…Teacher entrepreneurs have shown to have good theoretical (Dennis & Parker, 2010;Hunzicker, 2017;Martin et al, 2018) and content knowledge of the topics they are teaching such as music (Bell, 2016;Nash, 2014). Experience in teaching has also been mentioned which can lead to better knowledge in both content and teaching methods (Amorim Neto et al, 2017). A "deep knowledge of students, families, and communities" is also part of the teaching and classroom related knowledge teacher entrepreneurs have (Berry, 2013a, p. 310).…”
Section: Social Value-oriented Teacher Entrepreneursmentioning
confidence: 99%
“…Satisfaction studies are applied to a wide range of fields. Such as academic job satisfaction (Shin and Jung, 2014), university satisfaction (Bowman and Smedley, 2013), career satisfaction (Lounsbury et al, 2012), student satisfaction (Douglas et al, 2015;Wang et al, 2019), and teachers' job satisfaction (Neto et al, 2017). In the field of entrepreneurship, Noorderhaven et al (2004) found that dissatisfaction at the level of societies has a positive and significant influence on self-employment levels.…”
Section: Introductionmentioning
confidence: 99%